THE EFFECTIVENESS OF USING DEBATE TECHNIQUE FOR LANGUAGE LEARNING - Kurbaniyazova, S. (SCIENCE and SOCIETY, 2025)
The article investigates the effectiveness of the debate technique as a pedagogical tool in enhancing language learning among English language learners. The research explores how structured debates impact learners’ speaking fluency, critical thinking, vocabulary development, and overall language confidence. Despite initial challenges such as anxiety and limited proficiency, students reported positive experiences and perceived noticeable progress in their language skills. The article concludes that incorporating debates into language instruction is a highly effective strategy to promote active learning and language development.